Diagnostic Skill of Internalization-Interconnection Qur’ani With Science in Three Levels of Madrasah - Wirawan Fadly; Fatkul Jannah; Omnia S. Ahmed; Diah susanti (Cendekia: Kependidikan dan Kemasyarakatan, 2020)
The study diagnosed the skill of internalization-interconnection of the Qur’ani with science at the three levels of Madrasah (Islamic school). We used a mixed-method research methodology, which was started with a cross-sectional survey, then continued with phenomenology. With this combination of research, it is hoped that more comprehensive data results will be obtained. The number of participants involved in the survey was 116 people taken randomly at three levels of the madrasah, who were then purposively classified based on the highest score for in-depth interviews. The collected data were analyzed using quantitative descriptive, qualitative descriptive, and inferential statistics through multivariate tests. The results of the present study show that: 1) the theoanthopocentric approach had been implemented quite well since the MI (Islamic Elementary School) level; 2) MTs (Islamic Junior High School) is the best level for optimizing the planting of the skill to internalize-interconnect Qur’ani with science; 3) the profile of students’ internalization skills in the MI is at the knowing level, MTs is in the responding level, and at the MA (Islamic Senior High School)in the organizing level, while the interconnection skill at the MI is in the understanding in textual level (textual), the MTs in the level of understanding contextually only on the initial experience of students (effective contextual) and MA in the level of understanding analyzes the relationship between science and other subjects as well as with the verses of the Qur’an in a structured manner (structured contextual).Tujuan penelitian adalah untuk mendiagnosa kemampuan internalisasi-intekoneksi Qur’ani dengan IPA di tiga jenjang pendidikan madrasah. Penelitian dilakukan melalui mix-method atau metode kombinasi yang diawali dengan cross sectional survey kemudian dilanjutkan dengan fenomenologi. Dengan penelitian kombinasi ini diharapkan mendapatkan hasil data yang lebih komprehensif. Jumlah partisipan yang terlibat dalam survey sebanyak 116 orang diambil secara random di tiga jenjang madrasah, yang kemudian dikrucutkan secara purpossive berdasarkan nilai tertinggi untuk diwawancarai secara mendalam. Data yang telah terkumpul kemudian dianalisa menggunakan deskriptif kuantitatif, deskriptif kualitatif, serta statistik inferensial melalui uji multivariat. Hasil penelitian menunjukkan bahwa: 1) pendekatan theoanthopocentris telah dilaksanakan secara cukup baik sejak jenjang MI; 2) jenjang MTs merupakan jenjang paling baik untuk untuk optimalisasi penanaman kemampuan internalisasi-interkoneksi al-Qur’an dengan IPA; 3) Profil keterampilan internalisasi siswa di MI ada di tingkat mengetahui, MTs di tingkat menanggapi, dan di MA di tingkat pengorganisasian, sedangkan keterampilan interkoneksi di MI ada di tingkat pemahaman pada tataran tekstual (tekstual), MTs pada tataran pemahaman kontekstual hanya pada pengalaman awal peserta didik (kontekstual efektif) dan MA pada tataran pemahaman menganalisis hubungan IPA dengan mata pelajaran lain serta dengan ayat-ayat al-quran secara terstruktur (kontekstual terstruktur)